Collider probes of axion-like particles - Bauer, Martin; Neubert, Matthias; Thamm, Andrea (Arxiv, 2017)
Axion-like particles (ALPs), which are gauge-singlets under the Standard Model (SM), appear in many well-motivated extensions of the SM. Describing the interactions of ALPs with SM fields by means of an effective Lagrangian, we discuss ALP decays into SM particles at one-loop order, including for the first time a calculation of the $a→πππ$ decay rates for ALP masses below a few GeV. We argue that, if the ALP couples to at least some SM particles with couplings of order $(0.01-1) TeV^{-1}$, its mass must be above 1 MeV. Taking into account the possibility of a macroscopic ALP decay length, we show that large regions of so far unconstrained parameter space can be explored by searches for the exotic, on-shell Higgs and $Z$ decays
Gesehen am 10.01.2018